Using wavelet transform in image processing - Daiyrbayeva, Elmira; Feodor, Murzin; Yerimbetova, Aigerim; Toigozhinovа, Ainur (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
At the present stage of globalization, the problem of information security remains relevant. It is necessary to commend the work of scientists in the areas of the possibility of delivering information in a confidential form by various methods. This issue is one of the priority areas in the field of steganography. This article discusses the possibility of using a wavelet transform for processing (improving) digital images by transferring them to the transformation domain, and after processing - restoration using the inverse transformation operation. Computer image processing involves the processing of digital images using a PC or specialized devices built on digital signal processors. In this case, image processing is understood not only to improve the visual perception of images, but also to classify objects that are performed during image analysis.